Moving towards low carbon mobility - Givoni, Moshe; Banister, David; Edward Elgar Publishing (Cheltenham : Edward Elgar Pub. Ltd., 2013)
For a thorough and thoughtful perspective on what it will take to de-carbonize cities of the future, this book is a must-read. Technology alone, we are told, will not create the post-carbon city. As important is coming to grips with a complex web of cultural, institutional, financial, and social factors that powerfully shape mobility choices, now and in the future. A balanced, holistic approach that reveals how the many elements of contemporary transport systems work together offers the best hope for achieving more sustainable, less carbon-intensive mobility futures. Robert Cervero, University of California, Berkeley, USThis is not just another book about transport and climate change. It sensibly places transport within the much broader concept of mobility and explores all aspects of travel behaviour, of people and goods, and the infrastructure needs to serve these, leading to a balanced set of policy proposals. This volume, compiled by an internationally eminent team of researchers, is essential reading for all those wanting a balanced and objective analysis of this critical topic. Roger Vickerman, University of Kent, UKA unique assemblage of papers by top international experts that together cover every aspect of the transport-mobility-environment relationship todays central issue for transport planners worldwide. Sir Peter Hall, University College London, UKThe transport sector has been singularly unsuccessful in becoming low carbon and less resource intensive. This book takes an innovative and holistic social, cultural and behavioural perspective, as well as covering the more conventional economic and technological dimensions, to provide a more complete understanding of the mobility and transport system and its progress towards high carbon mobility.The book uses this platform to explore the means to achieve low carbon mobility through outlining alternative pathways, through an investigation of theories of change, and through alternative visions of the low carbon transport city. The books core message is that the complexity of the mobility and transport system should not encourage inaction, but strong and immediate action. In addition to implementing a wide range of policy measures, the book argues for a fundamental change in thinking when it comes to transport policy, governance and analysis approaches, before low carbon mobility becomes a reality.Bringing together the latest thinking on transport, mobility and the environment, this book will appeal to researchers and students interested in sustainability issues and sustainable transport and transport related areas in particular, including policy makers as well as a more general professional audience.
pt. I. Key elements in the mobility and transport system -- pt. II. Towards low carbon mobility.
Includes bibliographical references and index.
Keywords: Transportation -- Environmental aspects; Carbon dioxide mitigation; Electronic books